Substitusi Tepung MOCAF (Modified Cassava Flour) dalam Pembuatan Bolu Kukus - Anggita Resthi; Zukryandry (Food Scientia : Journal of Food Science and Technology, 2021)
This research is aimed to know the best formulation and sensory qualitycharacteristics of mocaf-based steamed sponge cake. The formulation used weremocaf flour and wheat flour with ratios of 20:80 (L1), 40:60(L2), 60 : 40 (L3), 80 :20 (L4), dan 100 : 0 (L5). Steamed cakes with formulation of 60% mocaf flour is themost liked overall in respect to their color, texture, taste, and smell attributes.Proximate analysis results for the best formulation shows carbohydrate value of42,30%, water content of 24,43%, ash content of 0,52%, insoluble fiber content of2,60%, protein content of 3,95%, dan fat content of 20,24%.